Chemical Modification of Glycoproteins’ Carbohydrate Moiety as a General Strategy for the Synthesis of Efficient Biocatalysts by Biomimetic Mineralization: The Case of Glucose Oxidase - Marija D. Stanišić (MDPI AG, 2021)
Zeolitic imidazolate framework-8 (ZIF-8) is widely used as a protective coating to encapsulate proteins via biomimetic mineralization. The formation of nucleation centers and further biocomposite crystal growth is entirely governed by the pure electrostatic interactions between the protein’s surface and the positively charged Zn(II) metal ions. It was previously shown that enhancing these electrostatic interactions by a chemical modification of surface amino acid residues can lead to a rapid biocomposite crystal formation. However, a chemical modification of carbohydrate components by periodate oxidation for glycoproteins can serve as an alternative strategy. In the present study, an industrially important enzyme glucose oxidase (GOx) was selected as a model system. Periodate oxidation of GOx by 2.5 mM sodium periodate increased negative charge on the enzyme molecule, from −10.2 to −36.9 mV, as shown by zeta potential measurements and native PAGE electrophoresis. Biomineralization experiments with oxidized GOx resulted in higher specific activity, effectiveness factor, and higher thermostability of the ZIF-8 biocomposites. Periodate oxidation of carbohydrate components for glycoproteins can serve as a facile and general method for facilitating the biomimetic mineralization of other industrially relevant glycoproteins.